2013
DOI: 10.1016/j.talanta.2013.04.057
|View full text |Cite
|
Sign up to set email alerts
|

On-chip electrochemical microsystems for measurements of copper and conductivity in artificial seawater

Abstract: The fabrication and characterisation of microelectrochemical sensors for Cu(2+) and conductivity suitable for operation in the marine environment are presented. The impact of the designs on sensor performance and their adequacy to operate in real conditions are discussed. The sensors, tailored to voltammetric and impedimetric measurements, are fabricated on silicon using photolithographic and thin film deposition techniques. The impedimetric sensor is made of Pt interdigitated electrodes which are used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…due to its inherent miniaturization, low-power 12 requirements, low limits of detection, compatibility with advanced 13 micromachining systems, low instrumentation cost, and relative 14 simplicity regarding to the procedure protocols [1][2][3]. Research 15 into new and effective electrode materials has been chiefly driven 16 in order to improve existing electrochemical sensing systems and 17 to design new ones.…”
Section: Q2mentioning
confidence: 99%
“…due to its inherent miniaturization, low-power 12 requirements, low limits of detection, compatibility with advanced 13 micromachining systems, low instrumentation cost, and relative 14 simplicity regarding to the procedure protocols [1][2][3]. Research 15 into new and effective electrode materials has been chiefly driven 16 in order to improve existing electrochemical sensing systems and 17 to design new ones.…”
Section: Q2mentioning
confidence: 99%
“…On the other hand, if the electrodes are dead, black dots were observed representing the absence of gold. Lithographic fabrication procedures used are known to be associated with the presence of dead or inactive electrodes which eventually lead to a lower limiting current [2,19,20]. For the microband electrode of B3, it is also observed that no gold layer left within the recess surface after several usages.…”
Section: Figurementioning
confidence: 99%
“…Thus, microfabricated electrochemical sensors with WE microelectrode array can provide sufficient sensitivity and achieve limits of detection required for practical applications [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence research in this area is still in its infancy. Examples to date include chemical sensors (Provin et al 2013), autonomous analytical devices for high spatial and temporal resolution (Legiret et al 2013;Rérolle et al 2013;Xi et al 2011), onchip electrochemical microsystems (Herzog et al 2013) and microbial ecology devices (Rusconi et al 2014;Seymour et al 2010).…”
Section: Introductionmentioning
confidence: 99%